2018
DOI: 10.1073/pnas.1808819115
|View full text |Cite
|
Sign up to set email alerts
|

Early metal use and crematory practices in the American Southeast

Abstract: Long-distance exchange of copper objects during the Archaic Period (ca. 8000-3000 cal B.P.) is a bellwether of emergent social complexity in the Eastern Woodlands. Originating from the Great Lakes, the Canadian Maritimes, and the Appalachian Mountains, Archaic-age copper is found in significant amounts as far south as Tennessee and in isolated pockets at major trade centers in Louisiana but is absent from most of the southeastern United States. Here we report the discovery of a copper band found with the crema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Based on this model, we provide evidence of a relatively direct and unmediated relationship between Archaic period communities in the Great Lakes, the coastal Atlantic southeast United States, and intervening areas, perhaps including the Ohio and Tennessee River Valleys. In our prior publications (Hill et al 2019; Sanger et al 2018), we demonstrated that a copper band 1 found among cremated human remains located on an island off the southeastern U.S. Atlantic coast was fashioned from materials that originated in the Great Lakes during the Archaic period. We revisit these finds and focus on the acts, contexts, and processes used to incinerate human bodies in both locales to argue that the shared use of cremation to handle the dead, something virtually absent elsewhere in the Archaic southeastern United States (Sassaman 2010:66–77), was not coincidental but rather reflects an exchange network that spanned more than 1,500 km and moved both objects and information.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Based on this model, we provide evidence of a relatively direct and unmediated relationship between Archaic period communities in the Great Lakes, the coastal Atlantic southeast United States, and intervening areas, perhaps including the Ohio and Tennessee River Valleys. In our prior publications (Hill et al 2019; Sanger et al 2018), we demonstrated that a copper band 1 found among cremated human remains located on an island off the southeastern U.S. Atlantic coast was fashioned from materials that originated in the Great Lakes during the Archaic period. We revisit these finds and focus on the acts, contexts, and processes used to incinerate human bodies in both locales to argue that the shared use of cremation to handle the dead, something virtually absent elsewhere in the Archaic southeastern United States (Sassaman 2010:66–77), was not coincidental but rather reflects an exchange network that spanned more than 1,500 km and moved both objects and information.…”
mentioning
confidence: 70%
“…We ran direct accelerator mass spectrometry (AMS) radiocarbon dates on a human cranial vault fragment found 2 cm above the copper band and a femur fragment immediately adjacent to it. Both dates are statistically identical and show the cremated individuals died about 4100–3980 cal BP, contemporaneous with the formation of the shell arc (Supplemental Table 1, lab numbers OxA-32446 and UCIAMS-130901; Sanger et al 2018:E7674). The material culture recovered from the pit supports the radiocarbon findings, as they include fiber-tempered pottery and stemmed projectile points, which are diagnostic of the Late Archaic (e.g., Sassaman 1993).…”
Section: Study Areamentioning
confidence: 98%
“…The ATG codon of VP1 was fused in frame directly to the sequence encoding the Xa recognition sequence by BcgI restriction and religation (a feature of the cloning vector) generating the VP1 expression vector pHB17\6. All vectors and the VP1 sequence were verified by DNA sequencing and restriction mapping [30] (Sequenase 2.0 TM Sequencing Kit ; USB-Amersham, Braunschweig, Germany).…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…Below the name of each variant is listed the following : the amino acid sequences of loops I and III respectively, and the restriction endonuclease or other method used to screen for positive clones. ' Kunkel ' refers to primer-directed mutagenesis by a modification [20] of the method of Kunkel et al [21]. ' Cassette ' refers to cassette replacement mutagenesis via SnaBI/partial NcoI digestion as described in the text.…”
Section: Scheme 2 Flow Chart For the Creation Of Mb-2 To Mb-13 By Sitmentioning
confidence: 99%
“…Restriction endonucleases and other enzymes were obtained from New England Biolabs (Mississauga, Ontario, Canada) unless indicated otherwise. Positive clones were identified by restriction endonuclease screening or sequencing (Scheme 2) ; protein sequences were verified by DNA sequencing [21] of both strands of the entire milk bundle protein gene. Oligonucleotides used for mutagenesis were synthesized with a Pharmacia LKB Gene Assembler Special DNA synthesizer (Pharmacia, Dorval, Quebec, Canada) at 200 nmol scale, with reagents and procedures supplied by the manufacturer.…”
Section: Mutagenesis Proceduresmentioning
confidence: 99%